Vaccine-induced immunity in elite athletes undergoing respiratory assessment - Turner, S.; Hull, J.; Jackson, A.; Ranson, C.; Kelleher, P.; Loosemore, M.; Shah, A. (European Respiratory Journal, 2020)
Background: Respiratory illness accounts for the greatest amount of lost training and competition time for Olympic athletes. Given the nature of athletes` lifestyles, involving frequent and long-haul travel alongside close proximity to large crowds during competitions, vaccine-induced humoral immunity to common viral and respiratory pathogens is critical. The aim of this study was to analyse vaccine-induced immune responses in a cohort of elite athletes.